Prospective study of the association between sport-related concussion and brain morphometry (3T-MRI) in collegiate athletes: study from the NCAA-DoD CARE Consortium. Issue 3 (11th September 2020) - Bobholz, Samuel A; Brett, Benjamin L; España, Lezlie Y; Huber, Daniel L; Mayer, Andrew R; Harezlak, Jaroslaw; Broglio, Steven P; McAllister, Thomas; McCrea, Michael A; Meier, Timothy B
Abstract : Objectives: To determine the acute and early long-term associations of sport-related concussion (SRC) and subcortical and cortical structures in collegiate contact sport athletes. Methods: Athletes with a recent SRC (n=99) and matched contact (n=91) and non-contact sport controls (n=95) completed up to four neuroimaging sessions from 24 to 48 hours to 6 months postinjury. Subcortical volumes (amygdala, hippocampus, thalamus and dorsal striatum) and vertex-wise measurements of cortical thickness/volume were computed using FreeSurfer. Linear mixed-effects models examined the acute and longitudinal associations between concussion and structural metrics, controlling for intracranial volume (or mean thickness) and demographic variables (including prior concussions and sport exposure). Results: There were significant group-dependent changes in amygdala volumes across visits (p=0.041); this effect was driven by a trend for increased amygdala volume at 6 months relative to subacute visits in contact controls, with no differences in athletes with SRC. No differences were observed in any cortical metric (ie, thickness or volume) for primary or secondary analyses. Conclusion: A single SRC had minimal associations with grey matter structure across a 6-month time frame.